Ownership Structure and Innovation: Is There a Real Link? - Raquel Ortega; Rosina Moreno; Jordi Surinach (European Regional Science Association (ERSA), 2003)
This work intends to analyse the influence that several aspects internal to the firm have on the firms' innovative output. Although the theoretical model is based in the literature on innovation, it pays special attention on the impact of ownership structure, as stated by the theory of the agent. We test different hypothesis related to variables which explain how the ownership structure adopted by a firm can lead into different innovative efforts, a topic which has barely been studied so far. We are especially interested in considering the type of control in the firm (national or international), the group of control in the decision making process (owner or contracted managers) and the financing structure. The analysis is made for a sample of Spanish firms given by the Survey of Entrepreneurial Strategies, an annual survey that provides information on Spanish manufacturing firms from 1990 to 1999.
Keywords: 330